A liaF codon deletion abolishes daptomycin bactericidal activity against vancomycin-resistant enterococcus faecalis (2013)
The genetic bases for antibiotic tolerance are obscure. Daptomycin (DAP) is a lipopeptide antibiotic with bactericidal activity against enterococci. Using time-kill assays, we provide evidence for the first time that a deletion of isoleucine in position 177 of LiaF, a member of the three-component regulatory system LiaFSR involved in the cell envelope response to antimicrobials, is directly responsible for a DAP-tolerant phenotype and is likely to negatively affect response to DAP therapy.